A molecular genetic assessment of the population structure and variation in two inshore dolphin genera on the east coast of South Africa - Smith-Goodwin, Jacqueline Anne (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1998)
Coastal dolphins on the South African east coast are threatened by degradation and loss of habitat as a result of increasing coastal development, industrial effluent and agricultural runoff. In addition, dolphins off the coast of KwaZulu-Natal have, for more than four decades, been heavily exploited through unchecked incidental capture in shark nets set at 45 beaches. In light of the high rate of mortality and apparent depletion of both species, the persistence of bottlenose (Tursiops truncatus) and humpback (Sousa chinensis) dolphins in that region has been questioned. Genetic variation in south east African dolphin populations was determined as a means of assessing the fitness of the populations and their resilience to demographic disturbances. Furthermore, in order to determine the effects of continued mortality on the KwaZulu-Natal subpopulations, it was necessary to determine whether they are open or closed to immigration from the adjacent East Cape region, which represents a relatively unstressed region, characterised by a lack of shark nets and less intensive coastal activities. Genetic variation and differentiation in the maternal genome was assessed by determining the sequence of the first 400 bases of the mtDNA control region in bottlenose and humpback dolphins from KwaZulu-Natal and the East Cape. Nuclear variation and differentiation was estimated at six microsatellite loci and compared with earlier estimates determined from allozyme electrophoresis. Random amplified polymorphic DNA (RAPD) was assessed as a means of identifying population subdivisions and diagnostic population markers. Both bottlenose and humpback dolphins on the South African east coast are characterised by low nuclear and organellar genetic variation, consistent with a possible genetic bottleneck, the inferred date of which coincides with the onset of the last glacial period. Genetic variation in South African bottlenose dolphins was lower than that reported elsewhere for the species, while an intraspecific comparison supported lower genetic variation in South African humpback dolphins than in humpback dolphins sampled off Hong Kong. An analysis of molecular variance (AMOVA), performed on mtDNA haplotype frequency data indicated, for both species, significant genetic subdivision, concordant with geographic location. The data suggested female bottlenose dolphins demonstrate regional philopatry, displaying limited movement between KwaZulu-Natal and the East Cape. Female humpback dolphins tend towards strict local philopatry, with significant maternal differentiation evident both within and between regional subdivisions. Differentiation in microsatellite allele frequencies was also demonstrated between KwaZulu-Natal and the East Cape for both species, suggesting that the movement of male bottlenose and humpback dolphins may also be restricted. Nonetheless, considerably higher nuclear gene flow estimates suggested that males of both species represent the principal vectors of gene dispersal. The implications of historically low genetic variability and population subdivision in South African dolphins are important in view of the current rate of mortality in KwaZulu-Natal. The persistence of coastal dolphin populations relies on their ability to recover following a bottleneck event. Continued removal of demographically important age-sex classes such as occurs in shark nets, may not only further reduce the genetic variation, but would ultimately deplete dolphin populations in KwaZulu-Natal beyond a sustainable number, resulting in eventual local extinction. The differentiation of the two regions implies that, in the event of local extinction occurring, dolphins, particularly females, from adjacent regions will not readily re-colonise the area. This would result in fragmentation of the south east African populations and ensure reproductive isolation from neighbouring populations on the east African coast.
Keywords: Dolphins -- South Africa; Variation (Biology); Dolphins -- Genetics; Population genetics; Bottlenose dolphin -- South Africa; Sousa -- South Africa